A Non-contact Heart Rate Measurement Approach Based on Modified EEMD Algorithm with Updated White-noise Iterating. Issue 1 (1st November 2022) - Shi, Yingli; Qiu, Jian; Peng, Li; Han, Peng; Luo, Kaiqing; Liu, Dongmei
Abstract: At present, Imaging Photoplethysmography (IPPG) has attracted extensive attention on heart rate measurement, because of its non-contact, non-invasive and safe characteristics. However, in reality, the IPPG signal is extremely feeble and susceptible to be submerged by ambient interference such as illumination. To this end, we propose a new IPPG signal processing approach to enhance the anti-interference capability of measuring heart rate through a modified EEMD algorithm with updated white-noise iterating. In the modified EEMD algorithm, based on the standard deviation of the input IPPG signal, zero-mean white noises are generated randomly for iterative ensemble averaging. Through this new method, the fault caused by the residual white noise of traditional EEMD is solved. Lastly, through the comparative experiments of our own acquisition statistics, the approach proposed by this paper has significantly improved the performance in terms of accuracy, timeliness and anti-interference under various scenarios. The mean absolute error reaches 1.4 beats per minute and the correlation coefficient r reaches 0.8089. In addition, the modified EEMD algorithm reduces the running time by more than 10 times compared to the original method, approximately 0.16s per time.